Polyelectrolyte - mediated adsorption of amelogenin monomers and nanospheres forming mono- or multi-layers - Gergely, Csilla (2007)
We have applied optical waveguide lightmode spectroscopy combined with streaming potential measurements and Fourier transformed infrared spectroscopy to investigate adsorption of amelogenin nanospheres onto polyelectrolytes. The long term objective was to better understand the chemical nature of these assemblies and to gain further insight into the molecular mechanisms involved during self-assembly. It was found that monolayers of monomers and negatively charged nanospheres of a recombinant amelogenin (rM179) irreversibly adsorbed onto a positively charged polyelectrolyte multilayer films. Based on measurements performed at different temperatures it was demonstrated that intermolecular interactions for the formation of nanospheres were not affected by their adsorption onto polyelectrolytes. Consecutive adsorption of nanospheres resulting in the formation of multilayer structures was possible by using cationic poly(L-lysine) as mediators. N-Acetyl-D-Glucosamine (GlcNac) did not disturb the nanosphere-assembled protein’s structure and it only affected the adsorption of monomeric amelogenin. Infrared spectroscopy of adsorbed amelogenin revealed conformational differences between the monomeric and assembled forms of rM179. While there was a considerable amount of α-helices in the monomers, β-turn and β-sheet structures dominated the assembled proteins. Our work constitutes the first report on a structurally controlled in-vitro buildup of an rM179 nanosphere monolayer-based matrix. Our data support the notion that amelogenin self-assembly is mostly driven by hydrophobic interactions and that amelogenin/PEM interactions are dominated by electrostatic forces. We suggest that similar forces can govern amelogenin interactions with non-amelogenins or the mineral phase during enamel biomineralization.